Ensino de Ciências Naturais em espaços educativos: o tema da exploração da seringa em uma perspectiva interdisciplinar - Oliveira, Ercilene do Nascimento Silva de (2021)
This work presents possibilities for pedagogical practices, specifically in the context of Hybrid Teaching using an element of nature, the rubber tree (Hevea brasiliensis) as a facilitator for Science Teaching in an interdisciplinary perspective. In times of pandemic, the virtual visit to a thematic museum was essential to arouse the interest, motivation, and interaction of the students participating in the research. Hence, the purpose of this work was to understand how interdisciplinarity practice takes place using hybrid teaching in the second year of high school, through the theme of the exploitation of the rubber tree in educational spaces. In methodological terms, this is a qualitative research with a descriptive and field study, having its philosophical foundation based on Merleau-Ponty’s (2018) phenomenological premises. The interdisciplinarity aspects are based on Fazenda (2003, 2011,2012, 2013, 2014), Japiassu (1976) and Lück (2013). We discussed Hybrid Teaching concepts by Kenski (2012) and Moran (2015) and Science Teaching by Chassot (2016), Delizoicov, Angotti and Pernambuco (2002), and Fachín-Terán (2013). For data collection, we used interviews, questionnaires, systematic observation, a virtual visit video, the didactic sequence with the natural element of the rubber tree, active practices such as Khoot, blog, QR-Codes, and the writing, through the argumentative essay. We took Bardin's categorical content analysis as the basis for the investigation of the collected data, from which we extracted the categories used in the inference of the results in our three research objectives. From the results, we realized that despite the physical distancing, the experience with the video brought sensations and sensory stimuli to the students, ratifying the phenomenological view beyond the experience lived in the face-to-face environment. As for facilities in this research, the technological resources available favor the interdisciplinary model in hybrid education. In the context of the difficulties, the facilitating technology may be a difficulty in view of the punctual inability of teachers in the face of internet resources. Regarding the virtual visit to the educational space, we can say that doing it brought perceptions similar to those caused in face-to-face excursions. Within the scope of pedagogical resources in the hybrid space, we observed that the active practice of learning leads to interdisciplinarity through the planning of actions based on the teaching modalities for which it is intended. Therefore, pedagogical practices in hybrid teaching collaborate for interdisciplinarity and make it possible to expand students' knowledge.